PENGARUH KEBIJAKAN PENGAMPUNAN PAJAK DAN MODERNISASI SISTEM INFORMASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Kussuari Kussuari; Puspahadi Boenjamin (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
This research’s aims to analyze the impact of the 2016 tax amnesty policy and modernization of tax information system on individuall taxpayers compliance. Independent variabels in this research are the 2016 tax amnesty policy, modernization of tax information system e-billing system, e-filing system and e-SPT system for individual taxpayer. The dependent variabel is the compliance of individual taxpayers. This reseach uses primary data, by giving questionnaires to respondents by online and meet directly the individual tax payers and filled by 168 respondents. Sampling method in this research uses purposive sampling method that are individual taxpayers that have NPWP and submit the tax amnesty 2016. Analysis uses the multiple regression analysis. The results of the analysis and hypothesis shows that variable 2016 tax amnesy policy,tax modernization e-filing system and e-Spt PPh have positive impact on individual taxpayer compliance. but tax modernization e-billing system for individual taxpayer have not impact on personal taxpayer compliance.